Effect of Temperature, Time and Diimide/Rubber Ratio on the Hydrogenation of Liquid Natural Rubber by Response Surface Methodology - Mohamad Shahrul Fizree Idris; Nur Hanis Adila Azhar; Fazira Firdaus; Siti Efliza Ashari; Siti Fairus Mohd Yusoff (Indonesian Journal of Chemistry, 2019)
Hydrogenated liquid natural rubber (HLNR) was synthesized from liquid natural rubber (LNR) by thermolysis of p-toluenesulfonyl hydrazide (TSH). The HLNR structure was characterized by Fourier-transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies. Thermogravimetric analysis (TGA) showed that the HLNR had higher decomposition temperature compared to LNR. A response surface methodology (RSM) based on a central composite rotatable design (CCRD) with five-level-three-factors was used to optimize the main important reaction parameters, such as the TSH:LNR weight ratio (1–3), reaction temperature (110–150 °C), and reaction time (1–8 h). A quadratic model was developed using this multivariate statistical analysis. Optimum conditions for the non-catalytic hydrogenation of LNR using TSH were obtained; an LNR hydrogenation percentage of 83.47% at a TSH:LNR weight ratio of 1.41, a reaction temperature of 118.11 °C, and a reaction time of 3.84 h were predicted. The R2 value of 0.9949 indicates that the model provides data that are well matched with those from the experiment.